2017
DOI: 10.1016/j.ajpath.2017.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cell Apoptosis and Amelioration of Pulmonary Fibrosis by Thrombomodulin

Abstract: Pulmonary fibrosis is the terminal stage of a group of idiopathic interstitial pneumonias, of which idiopathic pulmonary fibrosis is the most frequent and fatal form. Recent studies have shown that recombinant human thrombomodulin (rhTM) improves exacerbation and clinical outcome of idiopathic pulmonary fibrosis, but the mechanism remains unknown. This study evaluated the mechanistic pathways of the inhibitory activity of rhTM in pulmonary fibrosis. Transgenic mice overexpressing human transforming growth fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…We performed radiological evaluation of the chest using a micro-CT (Latheta LCT-200, Hitachi Aloka Medical, Tokyo, Japan). Mice received isoflurane inhalation as anesthesia and were placed in a prone position for data acquisition 67 . Six specialists in respiratory diseases blinded to the treatment groups scored the chest CT findings based on the following criteria: score 1, normal lung findings; 2, intermediate findings; 3, slight lung fibrosis; 4, intermediate findings; 5, moderate lung fibrosis; 6, intermediate findings; and 7, advanced lung fibrosis ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We performed radiological evaluation of the chest using a micro-CT (Latheta LCT-200, Hitachi Aloka Medical, Tokyo, Japan). Mice received isoflurane inhalation as anesthesia and were placed in a prone position for data acquisition 67 . Six specialists in respiratory diseases blinded to the treatment groups scored the chest CT findings based on the following criteria: score 1, normal lung findings; 2, intermediate findings; 3, slight lung fibrosis; 4, intermediate findings; 5, moderate lung fibrosis; 6, intermediate findings; and 7, advanced lung fibrosis ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Six specialists in respiratory diseases blinded to the treatment groups scored the chest CT findings based on the following criteria: score 1, normal lung findings; 2, intermediate findings; 3, slight lung fibrosis; 4, intermediate findings; 5, moderate lung fibrosis; 6, intermediate findings; and 7, advanced lung fibrosis ( Supplementary Fig. 1a) 67 . We used the Ashcroft lung fibrosis score and the hydroxyproline content of the lungs to validate the CT findings ( Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recombinant human soluble TM (rhTM) was approved in 2008 and has been used for treatment of disseminated intravascular coagulation in Japan. Recently, the antifibrotic efficacy of rhTM has been reported [3,4]. Several studies have shown its therapeutic effects on acute exacerbation of idiopathic pulmonary fibrosis, which is pathophysiologically characterized by extravascular and intra-alveolar thrombin activation and fibrin deposition following epithelial and endothelial injury [5,6].…”
Section: Introductionmentioning
confidence: 99%